The lymphocyte levels of Hashimoto thyroiditis patients were significantly lower than that of healthy population - Hui Xue; Ruyi Xu (Frontiers in Endocrinology)
Background and purposeHashimoto thyroiditis (HT) is an autoimmune disease without infectivity. We compared the differences of blood lymphocytes levels between HT patients and healthy people.Patients and methodsThis study included a total of 84 HT patients whose thyroid function was normal and 60 HT patients with abnormal thyroid function. A corresponding number of medical examination population in our hospital were randomly selected as the control groups. White blood cell count, neutrophil count, neutrophil percentage, lymphocyte count, and lymphocyte percentage were compared between HT patients and healthy population. The correlations between TSH, FT4 and above parameters were further tested.ResultsWe found significant differences between HT with normal thyroid function group and control group in lymphocyte count (P<0.001), lymphocyte percentage (P<0.001) and neutrophil percentage (P<0.001), but no differences in sex (P=0.134), age (P=0.200), white blood cell count (P=0.315) and neutrophil count (P=0.790). Significant differences were observed in neutrophil count (P=0.032), neutrophil percentage (P=0.010), lymphocyte count (P=0.010) and lymphocyte percentage (P<0.001) between HT with abnormal thyroid function group and control group, but not in sex (P=0.769), age (P=0.060) and white blood cell count (P=0.156) between the two groups. There were significant differences in white blood cell count (P=0.009) and neutrophil count (P=0.032) between HT patients in the normal thyroid function group and HT patients in the abnormal thyroid function group. Neither FT4 nor TSH was associated with lymphocyte levels or neutrophil levels.ConclusionsThe lymphocyte levels in HT patients were significantly lower than healthy population. The neutrophil count in HT patients with regular thyroid function was lower than those in abnormal thyroid function HT patients.